Zależność pomiędzy konsumpcją a stopą procentową w Polsce - Utzig, Monika (The Dependence Between Consumption and Interest Rate in Poland, 2009)
Consumption expenditures of households are determined by the level of interest rates. When interest rates are higher, households delay consumption. In the paper, the dependence between consumption and interest rate in Poland was studied. The correlation coefficient between consumption and interest rate was calculated on the basis of data covering period from the first quarter of 1996 to the forth quarter of 2008. Next, models of consumption with taking account of interest rate were estimated. Three forms of consumption function were used: simple consumption function in the form proposed by Keynes, consumption function consistent with the life-cycle hypothesis of Modigliani and consistent with the theory of permanent income of Friedman. In all the models interest rate turned out to be statistically significant and consumption expenditures decrease with an increase of interest rate. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 423-430